Paper towns ebook - Green, John (2008)
Winner of the Edgar Award The #1 New York Times  Bestseller Publishers Weekly and USA Today Bestseller Millions of Copies Sold Q uentin Jacobsen has spent a lifetime loving the magnificent Margo Roth Spiegelman from afar. So when she cracks open a window and climbs back into his life—summoning him for an ingenious campaign of revenge—he follows. When their all-nighter ends and a new day breaks, Margo has disappeared. But Q soon learns that there are clues—and they’re for him. Embarking on an exhilarating adventure to find her, the closer Q gets, the less he sees the girl he thought he knew. #1 Bestselling author of The Fault in Our Stars John Green crafts a brilliantly funny and moving coming-of-age journey about true friendship and true love.